2016
DOI: 10.3928/01484834-20161114-06
|View full text |Cite
|
Sign up to set email alerts
|

Critical Care Interprofessional Education: Exploring Conflict and Power—Lessons Learned

Abstract: The findings suggest that students experience interprofessional conflict in clinical settings, yet lack the confidence and skills to effectively mitigate these behaviors. Ongoing studies to measure student empowerment and their intentions to practice collaboratively before and after graduation are recommended. [J Nurs Educ. 2016;55(12):696-700.].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Accordingly, addressing perceived gaps in knowledge, dissemination, team roles, and inter-professional communication is essential [ 27 , 28 ]. In addition to simulation training mentioned previously, other solutions for improved communication include training programs on cultural humility, conflict resolution, reinforcing aligned objectives that attend to skills specific to each discipline, and post-intubation clinical or “hot” debriefs [ 26 , 27 , 29 31 ]. The lessons learned from this rapidly implemented and high-acuity collaboration will remain pertinent as external personnel continue to play active roles in ED care [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, addressing perceived gaps in knowledge, dissemination, team roles, and inter-professional communication is essential [ 27 , 28 ]. In addition to simulation training mentioned previously, other solutions for improved communication include training programs on cultural humility, conflict resolution, reinforcing aligned objectives that attend to skills specific to each discipline, and post-intubation clinical or “hot” debriefs [ 26 , 27 , 29 31 ]. The lessons learned from this rapidly implemented and high-acuity collaboration will remain pertinent as external personnel continue to play active roles in ED care [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on Friend et al . study, medical and nursing students believed that to succeed in their career, they need to create effective communication in a team and cooperate with each other in clinical settings [ 37 ]. Also, Zweibel's study showed that students considered conflicts in healthcare teams to be essential for growth and beneficial, and in their opinion, how to manage conflicts was important.…”
Section: Discussionmentioning
confidence: 99%
“…The concepts of the five items of this subscale show that acquiring conflict management competency is a necessary qualification for students to play a professional role as a member of the healthcare team in future and to establish effective communication with other team members. Based on Friend et al study, medical and nursing students believed that to succeed in their career, they need to create effective communication in a team and cooperate with each other in clinical settings [37]. Also, Zweibel's study showed that students considered conflicts…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we found the categories from the data flow. In this approach, researchers immerse in the data to allow new insights tofind, also described as inductive category development [ 32 , 33 ].…”
Section: Methodsmentioning
confidence: 99%